COMPARATIVE CLINICAL FEATURES OF MESOTYMPANITIS AND EPITYMPANITIS - Akhundjanov N.A. (Web of Journals Publishing, 2025)
Chronic suppurative otitis media (CSOM) is a persistent inflammatory process of the middle ear and mastoid cavity characterized by tympanic membrane perforation and recurrent otorrhea. Clinically, two major forms are distinguished — mesotympanitis (safe type) and epitympanitis (unsafe type) — which differ in their anatomical localization, clinical course, and potential complications. Objective. The purpose of this study was to conduct a comparative analysis of clinical manifestations, otoscopic findings, and complication rates between mesotympanitis and epitympanitis based on a cohort of patients with chronic otitis media. Materials and Methods. A total of 120 patients (240 ears) with CSOM were examined at the Department of Otorhinolaryngology, Tashkent State Medical University, from 2022 to 2024. Among them, 68 (56.6%) had mesotympanitis and 52 (43.4%) had epitympanitis. All patients underwent detailed otoscopic evaluation, pure-tone audiometry, temporal bone CT, and microbiological culture of ear discharge. Results. Mesotympanitis predominantly involved central perforation of the pars tensa, moderate conductive hearing loss (average 38 ± 5 dB), and mucous otorrhea. In contrast, epitympanitis presented with attic or marginal perforation of the pars flaccida, purulent fetid otorrhea, and mixed or sensorineural hearing loss (average 55 ± 7 dB). Bone erosion of the scutum and ossicular necrosis were observed in 64% of epitympanitis cases but only in 8% of mesotympanitis. Intracranial complications occurred exclusively in epitympanitis (7.6%). Conclusion. Mesotympanitis represents a benign, localized form of CSOM, whereas epitympanitis is a more aggressive, potentially dangerous variant associated with cholesteatoma formation and destructive changes in the temporal bone. Early differentiation between these forms using otoscopic and imaging criteria is essential for timely surgical intervention and prevention of life-threatening complications.
Keywords: Chronic otitis media, mesotympanitis, epitympanitis, cholesteatoma, clinical comparison.